Metabolic Engineering of Escherichia coli for Production of Mixed-Acid Fermentation End Products - Förster, Andreas H.; Gescher, Johannes (Frontiers in Bioengineering and Biotechnology, 2014)
Mixed-acid fermentation end products have numerous applications in biotechnology. This is probably the main driving force for the development of multiple strains that are supposed to produce individual end products with high yields. The process of engineering Escherichia coli strains for applied production of ethanol, lactate, succinate, or acetate was initiated several decades ago and is still ongoing. This review follows the path of strain development from the general characteristics of aerobic versus anaerobic metabolism over the regulatory machinery that enables the different metabolic routes. Thereafter, major improvements for broadening the substrate spectrum of Escherichia coli towards cheap carbon sources like molasses or lignocellulose are highlighted before major routes of strain development for the production of ethanol, acetate, lactate and succinate are presented.